FieldNA: a 3D printed vertical microfluidic device for portable nucleic acid isolation from olive oil samples - Penumarthy, Vineet; Dourou, Athanasia-Maria; Lampropoulou, Evangelia; Arhondakis, Stilianos; Prakash, Ravi (Frontiers in Bioengineering and Biotechnology, 2025)
Isolation and purification of nucleic acid is an essential step in molecular assays for several application areas including healthcare, food safety and security, environmental monitoring, forensic science, etc. Nucleic acid extraction is a critical bottleneck towards field deployable nucleic acid-based assays, limiting them to laboratory setups and bench-top configurations. In addition, this lack of portability leads to longer timelines for sample processing and time-to-results, and higher testing costs, limiting access to this highly sensitivity assay tool in many instances. Several efforts have explored the creation of portable nucleic acid extraction systems to complement recent innovations in reducing the footprint and overhead of the nucleic acid test assays; however, most solutions are dependent on supporting systems such as power supply, and peripheral laboratory equipment (centrifuges, incubators). In this work, we present a novel 3D printed and fully disposable device, FieldNA, which minimizes specialized reagents and laboratory equipment requirements for nucleic acid extraction. The device relies on gravity driven vertical flow, and a magnet assisted bead washing and solid-liquid separation phase. Its functionality is demonstrated through DNA extraction from olive oil samples, and its performance is compared to three widely used extraction methods: CTAB combined with phenol chloroform (PCl), and two commercial filter column-based DNA extraction kits. The optimized FieldNA device prototype repeatably produced nucleic acid yield and quality comparable to the above lab-based olive oil DNA extraction techniques. The 3D printed device’s performance in isolating olive DNA from different batches of olive oil samples indicates its suitability for handling complex agricultural products, and the viable scalability for implementation in a wide spectrum of applications ranging from food to health sector.